(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The possibility of transmission of microorganisms to both humans and animals is considered a serious threat, due to the dissemination and high prevalence of antibiotic resistance among bacteria isolated from pet foods and animal proteins which presents as a serious issue to public health. The objective of this study was to evaluate the prevalence and pattern of antimicrobial resistance in bacterial pathogens which were isolated from animal proteins, fisheries, and pet foods. A total of 20 samples were collected and analyzed for the presence of bacterial species.